2014
DOI: 10.1530/eje-13-0961
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in GH response to GHRH+ARG in lipodystrophic patients with HIV: a key role for body fat distribution

Abstract: Objective: Gender influence on GH secretion in human immunodeficiency virus (HIV)-infected patients is poorly known. Design and methods: To determine the effect of gender, we compared GH response to GH-releasing hormone plus arginine (GHRHCArg), and body composition in 103 men and 97 women with HIV and lipodystrophy. The main outcomes were IGF1, basal GH, GH peak and area under the curve (AUC) after GHRHCArg, body composition, visceral adipose tissue (VAT), and subcutaneous adipose tissue (SAT). Results: Men h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
6
1
2
Order By: Relevance
“…A principal divergência diz respeito ao acúmulo de gordura no tronco, caracterizada pela obesidade abdominal, sendo um componente obrigatório na definição da IDF, com valores limítrofes menores do que os estabelecidos pelo NCEP-ATP III e AHA/NHLBI, salientando a importância de constituir medidas específicas por etnias. 12 Estudos com resultados conflitantes mostram os efeitos da SL sobre a SM em pacientes infectados pelo HIV, 11,[14][15][16][17][18][19][20][21] do impacto que as diferenças sexuais promovem, 3,4,5 ou mesmo se homens e mulheres deveriam se submeter a formas similares de TARV. 6 Dada a esta controvérsia, o objetivo deste estudo foi avaliar os efeitos da SL sobre os parâ-metros utilizados para diagnóstico da SM para cada sexo, em pacientes que vivem com HIV/aids em uso da TARV.…”
Section: Increased Chance Of Metabolic Syndrome In Women Living With unclassified
See 1 more Smart Citation
“…A principal divergência diz respeito ao acúmulo de gordura no tronco, caracterizada pela obesidade abdominal, sendo um componente obrigatório na definição da IDF, com valores limítrofes menores do que os estabelecidos pelo NCEP-ATP III e AHA/NHLBI, salientando a importância de constituir medidas específicas por etnias. 12 Estudos com resultados conflitantes mostram os efeitos da SL sobre a SM em pacientes infectados pelo HIV, 11,[14][15][16][17][18][19][20][21] do impacto que as diferenças sexuais promovem, 3,4,5 ou mesmo se homens e mulheres deveriam se submeter a formas similares de TARV. 6 Dada a esta controvérsia, o objetivo deste estudo foi avaliar os efeitos da SL sobre os parâ-metros utilizados para diagnóstico da SM para cada sexo, em pacientes que vivem com HIV/aids em uso da TARV.…”
Section: Increased Chance Of Metabolic Syndrome In Women Living With unclassified
“…2 Esta alteração lipodistrófica manifesta-se de maneira distinta entre os sexos. [3][4][5][6] Enquanto nos homens é caracterizada essencialmente pela redução da gordura periférica (Lipoatrofia) em membros, glúteos e na face, nas mulheres a tendência é de maior acúmulo (Lipohipertrofia) na região do tronco, 3,5 acarretando efeitos metabólicos mais pronunciados no sexo feminino. 7 Dislipidemias e alterações no metabolismo da glicose também são observadas nos pacientes com SL, 2,8,9,10 aumentando o risco do desenvolvimento de síndrome metabóli-ca (SM), 11 condição que eleva sobremaneira a morbidade do paciente HIV positivo.…”
Section: Introductionunclassified
“…[10] In our study we found BH in the female patients only and; limb and facial lipoatrophy with central obesity mainly in male ATA patients. This gender difference in ATA presentation might be due to hormones [11,12] along with differences in drug transport and metabolizing enzymes. [13] The HIV-associated ATA was first described in 1998, shortly after the introduction of PIs.…”
Section: Pictures Showing "Buffalo Hump" In a Woman On Art Drugs A) Bmentioning
confidence: 99%
“…releasing hormone (GHRH) plus Arginine (Arg) (GHRH + Arg) test is, in fact, higher than in healthy controls [2][3][4][5]. Gender [6] and adipose tissue redistribution, typical of patients treated with Highly Active Antiretroviral Therapy (HAART), called HIV-associated lipodystrophy syndrome [1] both contribute to determine the impairment of GH secretion in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, visceral fat seems to be a predictor of overnight GH levels [14]. However, GHD in HIV-infected patients is not thoroughly justified by the effect of visceral adiposity [2,4,5], which otherwise accounts for gender differences in GH secretion [6]. Moreover, it is not easy to define whether the GHD or the increase in visceral adiposity came first, because the increase in visceral fat disturbs the GH secretion [11,12], but it is also a consequence of GHD [15][16][17].…”
Section: Introductionmentioning
confidence: 99%